2012
DOI: 10.1159/000341683
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and Oxidative Stress in PCOS

Abstract: Polycystic ovary syndrome (PCOS) is a common metabolic and reproductive disorder in women. An increased cardiovascular risk has to be anticipated in PCOS as it is a metabolically unstable condition. Among cardiovascular risk factors, dyslipidemia is certainly the most persistent and highly prevalent. Predominant observation is an elevation of LDL cholesterol in all PCOS patients. Decreased concentrations of HDL cholesterol are found in obese PCOS from the third decade of life onwards while triglycerides start … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 27 publications
2
83
0
1
Order By: Relevance
“…34,35 An interesting issue is the finding that supplementation with omega-3, α-lipoic acid and N-acetyl cysteine results in an antioxidant, anti-inflammatory effect, improves insulin sensitivity and the lipid profile of women with PCOS. 36 Salehpour et al demonstrated that N-acetyl cysteine lowers levels of testosterone, reduces androgen response to gonadotropin stimulation, improves ovulation rates and long-term health after 6 months of treatment. 37 In recent years, attention has also been paid to the role of increased activity of the sympathetic nervous system in the pathogenesis, progression and treatment of PCOS.…”
Section: New Therapeutic Optionsmentioning
confidence: 99%
“…34,35 An interesting issue is the finding that supplementation with omega-3, α-lipoic acid and N-acetyl cysteine results in an antioxidant, anti-inflammatory effect, improves insulin sensitivity and the lipid profile of women with PCOS. 36 Salehpour et al demonstrated that N-acetyl cysteine lowers levels of testosterone, reduces androgen response to gonadotropin stimulation, improves ovulation rates and long-term health after 6 months of treatment. 37 In recent years, attention has also been paid to the role of increased activity of the sympathetic nervous system in the pathogenesis, progression and treatment of PCOS.…”
Section: New Therapeutic Optionsmentioning
confidence: 99%
“…Whether HbA1c is superior to OGTT regarding long-term metabolic and cardiovascular risk in PCOS must be established in prospective studies. It was estimated that 70% newly diagnosed women with PCOS had borderline or high lipid levels (33), including increased total cholesterol, TG, LDL or decreased HDL levels (34,35). In a Danish study population with median BMI 27 kg/m 2 , 41% patients with PCOS had HDL <1.29 mmol/L and 21% patients had TG >1.68 mmol/L (36).…”
Section: Cardiometabolic Disease In Pcosmentioning
confidence: 99%
“…In addition, due to increased production of free radicals and reactive oxygen species (ROS) [4], elevated circulating protein carbonyls, tumor necrosis factor-α (TNF-α), and decreased insulin signaling [5,6], it is associated with increased biomarkers of inflammation and oxidative stress. Increased inflammatory factors and biomarkers of oxidative stress among patients with PCOS may predict the development of cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM) [7][8][9].…”
Section: Affiliationsmentioning
confidence: 99%